Hubungan Paparan Media Cetak Dan Elektronik Dengan Tingkat Pengetahuan Pencegahan Demam Berdarah Dengue (DBD) di Wilayah Kerja Puskesmas Tarogong - Elang M Atoilah; Andhika Lungguh Perceka; Reren Reni Rahayu (Jurnal Medika Cendikia, 2015)
The high incidence of dengue fever based on health department Garut data in Tarogong Kaler subdistricts in 2014 in were 212 cases with a total population of 28.825. It was included as 3rd higest in Garut district. In the public health centers of Tarogong, there were 37 cases of Dengue Hemoragic Fever and 195 patiensc cases.The purpose of this study was to determine the relationship between print, electronic media exposure and the level of knowledge of prevention of dengue hemorrhagic fever (DHF) in the public health centers of Tarogong area. This research method was descriptive correlation with control design, with the proportion of sample 1: 1 ie 80 respondents. Data collection techniques to measure the level of knowledge (DHF) was usied a questionnaire, and using chi-square statistical test. The result study showed that almost all patients (60%) was exposed by print and electronic media and 40% was not exposed by print and electronic media with P-Value = 0.029. There was a significant relationship between exposure to the print and electronic media with the level of knowledge of the prevention of dengue hemorrhagic fever. Therefore, it is necessary efforts to increase knowledge about DHF prevention.